2015
DOI: 10.1038/jp.2015.81
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic thiol-disulfide homeostasis in hyperemesis gravidarum

Abstract: Native and total thiol were deficient in the hyperemesis gravidarum group and this deficiency was correlated with the severity of the disease. The thiol-disulfide balance has shifted to the oxidative side. This metabolic disturbance may have a role in the pathogenesis of hyperemesis gravidarum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 45 publications
0
25
0
Order By: Relevance
“…Knowing the function of thiols involved in the antioxidant system is therefore becoming increasingly important in terms of understanding several diseases associated with oxidative stress, including COPD [19]. Studies investigating the relation between oxidative stress and TDH have shown that such homeostasis is impaired in oxidative terms in patients with acute myocardial infarction, migraine, alopecia or chronic urticaria, in pregnant women with hyperemesis gravidarum (compared to normal gravidas), and in workers exposed to polycyclic aromatic hydrocarbons [14][15][16][33][34][35]. Babaoglu et al [36] assumed the presence of oxidative stress in COPD and investigated TDH in other subgroup diseases causing lower airway obstruction, such as asthma and asthma-COPD overlap syndrome (ACOS).…”
Section: Discussionmentioning
confidence: 99%
“…Knowing the function of thiols involved in the antioxidant system is therefore becoming increasingly important in terms of understanding several diseases associated with oxidative stress, including COPD [19]. Studies investigating the relation between oxidative stress and TDH have shown that such homeostasis is impaired in oxidative terms in patients with acute myocardial infarction, migraine, alopecia or chronic urticaria, in pregnant women with hyperemesis gravidarum (compared to normal gravidas), and in workers exposed to polycyclic aromatic hydrocarbons [14][15][16][33][34][35]. Babaoglu et al [36] assumed the presence of oxidative stress in COPD and investigated TDH in other subgroup diseases causing lower airway obstruction, such as asthma and asthma-COPD overlap syndrome (ACOS).…”
Section: Discussionmentioning
confidence: 99%
“…The thiol-disulfide balance is a significant member of various processes consisting of antioxidant defense, immune response, modulation of enzyme activity, and apoptosis (26). Dynamic thiol-disulfide homeostasis is implicated in several disorders (27,28). For example, it has been demonstrated that impaired thiol-disulfide balance has been involved in a variety of diseases such as myocardial infarction, preeclampsia, polycystic ovary syndrome, diabetes mellitus, and cancer (29).…”
Section: Discussionmentioning
confidence: 99%
“…Due to this carnage, there is correlation between the degree of ketonuria and HG [17]. While there is a negative correlation between disease severity and native thiol and total thiol, a positive correlation is detected between disulfide [18]. The American College of Obstetricians and Gynecologists (ACOG) currently recommends that a combination of oral pyridoxine hydrochloride (vitamin B6) and doxylamine succinate be used as first-line treatment for nausea and/or vomiting during pregnancy if pyridoxine monotherapy does not relieve symptoms [19].…”
Section: Discussionmentioning
confidence: 99%